2015
DOI: 10.6061/clinics/2015(08)02
|View full text |Cite
|
Sign up to set email alerts
|

Ocular risk management in patients undergoing general anesthesia: an analysis of 39,431 surgeries

Abstract: OBJECTIVE:This study sought to describe and analyze ocular findings associated with nonocular surgery in patients who underwent general anesthesia.METHODS:The authors retrospectively collected a series of 39,431 surgeries using standardized data forms.RESULTS:Ocular findings were reported in 9 cases (2.3:10,000), which involved patients with a mean age of 58.9±19.5 years. These cases involved patients classified as ASA I (33%), ASA II (55%) or ASA III (11%). General anesthesia with propofol and remifentanil wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Of the various causes of POVL, three main groups of pathologic entities have been identified that may be responsible for POVL ischemic optic neuropathy (ION), central retinal artery occlusion (CRAO) and cortical blindness. 1 , 2 , 3 , 4 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the various causes of POVL, three main groups of pathologic entities have been identified that may be responsible for POVL ischemic optic neuropathy (ION), central retinal artery occlusion (CRAO) and cortical blindness. 1 , 2 , 3 , 4 …”
Section: Discussionmentioning
confidence: 99%
“…PION comprises 3 types:arteritic PION, non-arteritic PION, and surgical PION as a complication of several systemic surgical procedures 1 , 2 , 3 , 4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DES affects up to 40% of the adult population and manifests as eye irritation, hyperemia, glare, eye fatigue, and blurred vision [2,3]. Etiologically, alterations in tear homeostasis are associated with dysfunction of the lachrymal and/or Meibomian glands (such as in Sjögren syndrome and Meibomian Gland Dysfunction (MGD)) as well as a number of other factors, including contact lens wearing, adverse effects of various medications, complications of ocular surgery and general anesthesia [1,[4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 A Brazilian retrospective study that included 39,431 patients submitted to non-ocular surgeries reported nine cases of ocular events (2.3:10,000), one case of which of blurry vision, and no cases related to visual loss. 6 …”
mentioning
confidence: 99%